Novel pulse sequences for time-resolved photo-CIDNP - Goez, M; Kuprov, I; Mok, K; Hore, P (2006)
The properties of a new class of pulse sequences for photo-CIDNP (photochemically induced dynamic nuclear polarization) are analysed in detail, and guidelines for their optimization and applicability are derived. Sensitivity is a central problem with time-resolved photo-CIDNP experiments. By using multiple laser flashes per acquisition and storing the polarizations temporarily in the spin system, a significant improvement is achieved. An alternative application is the reduction of the absorbed light needed to attain a given sensitivity. Compared to conventional signal averaging with the same number n of flashes, a maximum additional improvement by a factor of slightly more than can be achieved in both cases. By an analysis of the transfer pathways, it is shown that multiplet signals and CIDNP multiplet effects can also be investigated in this way, even for strongly coupled spin systems. Experimental examples are given.